Statistical testing and spatio-temporal evolution characteristics of the coupling coordination between green agricultural production efficiency and food security. - Tianao Li; Yue Hu (PLoS ONE)
Under the requirements of developing new quality productivity, balancing green agricultural development with food security has become crucial for sustainable development, particularly in regions facing environmental constraints. This study investigates the coupling coordination relationship between agricultural green development efficiency and food security in China's agricultural system. Using panel data from 31 Chinese provinces (2010-2022), the study employs a comprehensive analytical framework combining the super-efficiency SBM-DEA model for efficiency measurement, the entropy TOPSIS method for food security evaluation, coupling coordination degree analysis, and multi-dimensional spatial analysis including regional difference decomposition, spatial correlation analysis, and kernel density estimation. The results reveal three distinct development phases: stable development (2010-2016, coordination degree 0.49-0.52), rapid improvement (2017-2018, peaking at 0.60), and stable adjustment (2019-2022, stabilizing around 0.54). Spatially, three high-value clusters have formed around Beijing-Tianjin-Hebei (average coordination degree 0.68), the Yangtze River Delta (0.76), and Heilongjiang (0.81). Significant regional disparities persist, with eastern regions maintaining stable high-level development (average coordination degree >0.65) and western regions generally remaining below 0.50. Despite facing structural development constraints, Western regions possess latent comparative advantages in ecological agriculture. Gini coefficient decomposition, Moran's index analysis, and kernel density estimation collectively reveal that between-region differences dominate inequality sources (36.19%-49.99%), with strengthening spatial agglomeration effects creating path-dependent regional stratification. The findings suggest that achieving coordinated development requires differentiated regional strategies: technology transfer leadership for high-coordination regions, sustainable intensification support for transitional regions, and comprehensive structural interventions for low-coordination areas. These insights provide practical guidance for developing agricultural new quality productivity while ensuring food security.